Do “your angels” weep? Level up of job satisfaction among nurses - Pankajakshan, Vyshakh; Girijammal, Remya; Tamilselvan, Dharani Sree; Pinheiro, Carol; Sunil, Tess Maria; Surendranathan Nair, Unnikrishnan; Kalireth Rajendran, Unnikrishnan; Sajeev, Vinayak; Zain, Wasim; Anakkallunkal Murugan, Varsha; Pulikan, Tania J.; Njani, Vaishakh (International Journal Of Community Medicine And Public Health, 2023)
Background: Nurses play a pivotal role in our healthcare. It is therefore crucial to assess the job satisfaction levels of nurses for the proper functioning of the healthcare system. The present study was to assess the job satisfaction levels among nurses in Alappuzha district. Assessment of Job satisfaction levels will help to implement ergonomically beneficial policies in the healthcare system. Methods: A hospital based cross sectional study was conducted among the nurses during the months of October- November, 2022. Convenient sampling was done and persons who were willing to take part in the study were distributed with a pretested questionnaire. Job satisfaction was analysed using the Minnesota job satisfaction scale. Data was collected and entered in Microsoft Excel. It was analysed using SPSS version 26. Chi square test was used to find out the association between variables. Results: Totally 63 nurses responded to the questionnaire. Of the total study participants, 73% were satisfied with their job and 23% were having neutral level of job satisfaction. Level of job satisfaction was associated with sleep satisfaction, met financial needs, assault or abuse faced at work and perceived workload. The results also showed that there is no association between the level of job satisfaction and demographic factors. Conclusions: From this study, three-fourth of the participants were satisfied with their job. Only small portion of participants were satisfied with responsibility, advancement, moral values, working conditions, institutional policies and practices. They were dissatisfied with independence and compensation provided at job.